Student Response in Using Smartphone-Assisted Augmented Reality Video in Learning - sandra Sukmaning Adji; Faizal Akhmad Adi Masbukhin; Ayu Fahimah Diniyah Wathi (Postgraduate, University of Mataram, 2023)
Smartphone-assisted video augmented reality was developed to facilitate students who want to study anywhere, and anytime. The material studied includes the presentation of information about the work procedures of a concept being practiced. This study aims to develop a prototype for Chemistry Learning Using Video Program-Based Augmented Reality Applications and to get student responses about the use of augmented reality videos practiced in chemistry learning. This study uses a research and development approach based on the ADDIE method which has five steps, namely: analysis, design, development, implementation, and evaluation. The activity was preceded by developing a video program and being validated by a media expert, followed by making markers and developing applications. The results of the development were tried 39 students, as well as 4 teachers. The data were obtained through a questionnaire and were analyzed by descriptive qualitative. The results showed that the Prototype Development for Chemistry Learning Using Video Program-Based Augmented Reality Applications has been developed. Students responded stated that Augmented Reality (AR) video shows were able to build an understanding of teaching materials (92.3%), provide an initial understanding before working in the laboratory (95.9%), introduce the object of the experiment to be carried out (100%), explain the procedure for using the tool easily (100%).